Unselected Use of Ultrathin Strut Biodegradable Polymer Sirolimus-Eluting Stent Versus Durable Polymer Everolimus-Eluting Stent for Coronary Revascularization. (September 2018) - Yamaji, Kyohei; Zanchin, Thomas; Zanchin, Christian; Stortecky, Stefan; Koskinas, Konstantinos C.; Hunziker, Lukas; Praz, Fabien; Blöchlinger, Stefan; Moro, Christina; Moschovitis, Aris; Seiler, Christian; Valgimigli, Marco; et al.
Abstract : Background: Biodegradable polymer sirolimus-eluting stents (BP-SESs) have been reported to be noninferior compared with durable polymer everolimus-eluting stents (DP-EES) in a randomized clinical trial. We sought to compare the efficacy and safety of an ultrathin strut BP-SES with a DP-EES in an all-comers population. Methods and Results: Among 7640 consecutive patients who underwent percutaneous coronary intervention between March 2011 and June 2015, 4638 patients were exclusively treated with BP-SES (N=1896; 3137 lesions) or DP-EES (N=2742; 4468 lesions). After propensity score matching within strata of clinical indications, the final study population consisted of 2902 matched patients (BP-SES 2406 lesions and DP-EES 2368 lesions). The primary device-oriented composite end point (DOCE) included cardiac death, target vessel myocardial infarction, and target lesion revascularization at 1 year. BP-SES (6.9%) was noninferior to DP-EES (8.0%) with respect to device-oriented composite end point (hazard ratio [HR], 0.85; 95% CI, 0.65–1.11; P for noninferiority <0.001; P for superiority=0.24). No differences in cardiac death (BP-SES, 2.3% versus DP-EES, 3.0%; HR, 0.76; 95% CI, 0.49–1.20; P =0.25), myocardial infarction (BP-SES, 4.6% versus DP-EES, 4.6%; HR, 1.00; 95% CI, 0.71–1.40; P =0.99), or target lesion revascularization (BP-SES, 2.8% versus DP-EES, 2.5%; HR, 1.11; 95% CI, 0.71–1.74; P =0.65) were observed. The rate of periprocedural myocardial infarction was comparable between the 2 groups (2.1% versus 2.2%; HR, 0.97; 95% CI, 0.59–1.58; P =0.89). The rate of definite stent thrombosis was similarly low throughout 1 year (BP-SES, 0.8% versus DP-EES, 0.8%; HR, 1.00; 95% CI, 0.45–2.22; P =1.00). Conclusions: In a consecutively enrolled percutaneous coronary intervention population reflecting routine clinical practice, BP-SES was noninferior to DP-EES for device-oriented composite end point at 1 year. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT02241291. Abstract : Supplemental Digital Content is available in the text.